Online Dispute Resolution: Changing Demand in Indian Judicial System: Adapting the Indian judicial system through Online Dispute Resolution (Journal of Advances and Scholarly Researches in Allied Education, 2020)
“The COVID-19 pandemic and the resulting need for social distancing measures have exacerbated the existing problem of backlogs in the Indian judicial system. There is a growing understanding that the best path forward is to use technology to transform the dispute resolution ecosystem to adapt to the changing demands of justice.”[1]Online Dispute Resolution (hereinafter ODR) widely implies debate goal components that abuse the solace and efficiency of the web and online communication sources. The term joins everything from the electronic recording of passages and correspondence of reports to online hearings. Like any component for question goal, associations should check different examinations to choose if ODR is fitting for their condition. Concerning recording and exchanging reports, electronic documenting is ordinarily logically beneficial, functional, earth heartfelt, and less inconvenient. Also, far off the hearing, which keeps an essential separation from development time, costs, and various accuses related to the eye to eye hearings, should conventionally be progressively profitable and less excessive for the parties.